The Impact of EWOM on Purchase Intentions by Mediating Brand Image, Satisfaction and Trust in E-commerce in Indonesia - Rizni Aulia Qadri; Fitriana Aidnilla Sinambela; Ana Ana (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2023)
Progress in various fields of life always gives rise to new ideas that meet consumer needs, one of which is in the field of trade. With the rapid development of information technology, it provides a more flexible space for business people to reach the market for their products. This has fueled the emergence and development of digital marketing This study aims to analyze the effect of EWOM on Purchase Intention by mediating Brand Image, Satisfaction, and Trust in e-commerce in Indonesia. The object of this study used 288 samples who had shopped through e-commerce. Data analysis used the SmartPLS analysis method. The results of the study show that there is a significant relationship between Electronic Word of Mouth (EWOM) and Purchase Intention. Meanwhile, Brand Image, Satisfaction, and Trust also have a significant effect on Purchase Intention directly or indirectly.